2012
DOI: 10.1111/mec.12095
|View full text |Cite
|
Sign up to set email alerts
|

Linking predator–prey interactions with exposure to a trophically transmitted parasite usingPCR‐based analyses

Abstract: Parasite transmission is determined by the rate of contact between a susceptible host and an infective stage and susceptibility to infection given an exposure event. Attempts to measure levels of variation in exposure in natural populations can be especially challenging. The level of exposure to a major class of parasites, trophically transmitted parasites, can be estimated by investigating the host's feeding behaviour. Since the parasites rely on the ingestion of infective intermediate hosts for transmission,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Thus, the implications of these modes of transmission may be of importance in disease ecology and evolution and need to be further studied. Luong et al (2013) have shown the usefulness of combining epidemiologic data and molecular analyses of the diet of the host to link predator-prey interactions with exposure to trophically transmitted parasites. Similar approaches could be used in future research regarding the systems analyzed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the implications of these modes of transmission may be of importance in disease ecology and evolution and need to be further studied. Luong et al (2013) have shown the usefulness of combining epidemiologic data and molecular analyses of the diet of the host to link predator-prey interactions with exposure to trophically transmitted parasites. Similar approaches could be used in future research regarding the systems analyzed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, this taxon has been recorded in several species of Peromyscus (P. gossypinus, P. leucopus, P. maniculatus, and P. polionotus;Dyer 1969;Grundman et al 1976;Kinsella 1991;Luong et al 2013;Quentin and Kinsella 1972) also in USA. In Mexico this species has been recorded in P. maniculatus in Hidalgo (Pulido-Flores et al 2005).…”
Section: Syphacia (Seuratoxyuris) Peromyscimentioning
confidence: 98%
“…Parasite-mediated changes in host behavior are a fascinating addition to this because the parasite manipulates the host phenotype and can lead to a potential nonlinear increase in transmission (Moore 2002, Poulin 2010. But how host behavior, outside of parasite-induced phenomena, relates to transmission dynamics needs further attention and is difficult to study (Altizer et al 2003, Kjaer et al 2008, Luong et al 2013. Empirically estimating and evaluating the importance of exposure heterogeneity, in a manner that is meaningful when the transmission of parasites is considered, is an emerging challenge.…”
Section: Introductionmentioning
confidence: 99%